2020
DOI: 10.1002/pbc.28629
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns and recommendations for pediatric image‐guided radiotherapy: A Children's Oncology Group report

Abstract: This report by the Radiation Oncology Discipline of Children's Oncology Group (COG) describes the practice patterns of pediatric image‐guided radiotherapy (IGRT) based on a member survey and provides practice recommendations accordingly. The survey comprised of 11 vignettes asking clinicians about their recommended treatment modalities, IGRT preferences, and frequency of in‐room verification. Technical questions asked physicists about imaging protocols, dose reduction, setup correction, and adaptive therapy. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Clinicians may be reluctant to perform daily CBCTs for fear of the added radiation dose to the patient but accept the small extra dose from daily kV orthogonal pair imaging. This mindset is particularly prevalent for pediatric treatments 5 . In an analysis performed to estimate the risk of cancer induction for pediatric patients undergoing kV or MV IGRT, an additional 0.5 breast cancer cases per 10 4 patient years (PY) and 0.08 lung cancers per 10 4 PY was found for kV CBCT 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians may be reluctant to perform daily CBCTs for fear of the added radiation dose to the patient but accept the small extra dose from daily kV orthogonal pair imaging. This mindset is particularly prevalent for pediatric treatments 5 . In an analysis performed to estimate the risk of cancer induction for pediatric patients undergoing kV or MV IGRT, an additional 0.5 breast cancer cases per 10 4 patient years (PY) and 0.08 lung cancers per 10 4 PY was found for kV CBCT 9 .…”
Section: Discussionmentioning
confidence: 99%
“…When imaging pediatric cases, some clinicians have elected not to use CBCT daily, but instead to perform lower dose orthogonal kV imaging daily or even weekly imaging 5 . This lack of full 3D information may reduce the patient positioning accuracy and understanding of changes in anatomy during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this was two‐fold: The low magnitude of imaging dose and the unavailability of tools to calculate it easily. On the other hand, there have been studies suggesting the benefit of knowing the imaging dose, especially for children 5,43,44 . So having a tool than can do so would be beneficial for those cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that an accurate dose calculation may be warranted for kilovoltage x rays in Image-Guided Radiotherapy (IGRT) due to potential long-term side effects of the imaging dose, especially for pediatric patients. [1][2][3][4][5] Such a dose calculation is not possible using commercial treatment planning systems 3,6 with the exception of a recent system proposed for pre-clinical studies. 7 Monte Carlo (MC), generally considered the gold standard method for this purpose, has been used to compute dose distributions from kilovoltage x rays.…”
Section: Introductionmentioning
confidence: 99%
“…For example, adjuvant flank RT is recommended for patients who have local stage III FHWT or stage IV with local stage III. 96 Local stage III refers to staging at the primary site regardless of metastases [see "Children's Oncology Group (COG) Staging of Wilms Tumor," available in these guidelines at NCCN.org]. Biopsy alone does not upstage a tumor to stage III for determining whether to give adjuvant RT.…”
Section: Radiation Therapymentioning
confidence: 99%